Extracorporeal Irradiation and Reimplantation with Total Hip Arthroplasty for Periacetabular Pelvic Resections: A Review of 9 Cases. (20th April 2016) - Chan, Lester Wai Mon; Imanishi, Jungo; Ngan, Samuel Y.; Chander, Sarat; Chu, Julie; Thorson, Renae; Pang, Grant; Choong, Peter
Abstract : We report the early results of nine patients with periacetabular malignancies treated with Enneking and Dunham type 2 resection and reconstruction using extracorporeally irradiated (ECI) tumour bone combined with total hip arthroplasty (THA). Diagnosis was chondrosarcoma in six patients, osteosarcoma in two patients, and metastatic renal cell carcinoma in one patient. All patients underwent surgical resection and the resected specimen was irradiated with 50 Gy in a single fraction before being prepared for reimplantation as a composite autograft. The mean follow-up was 21 months (range, 3–59). All patients were alive at latest follow-up. No local recurrence was observed. One patient serially developed three pulmonary metastases, all of which were resected. One experienced hip dislocation due to incorrect seating of an acetabular liner. This was successfully treated with revision of the liner with no further episodes of instability. There were no cases of deep infection or loss of graft. The average Musculoskeletal Tumor Society (MSTS) score was 75% (range, 57–87%). Type 2 pelvic reconstruction with ECI and THA has shown excellent early oncological and functional results in our series. Preservation of the gluteus maximus and hip abductors is important for joint stability and prevention of infection.